Influence of Dynamic Magnetic Field Exposure Duration on the Germination and Growth of Khao Dawk Mali 105 Rice Seed - Tiwanat Gaewsondee; Cherdpong Chiawchanwattana; Phirayot Khaengkan; Juckamas Laohavanich; Chanat Vipattanaporn; Suphan Yangyuen (Agronomy)
Magnetic field (MF) priming provides a chemical-free alternative to conventional methods; however, static exposure approaches are often limited by spatial heterogeneity in field–seed interaction caused by fixed seed positioning, undermining both treatment uniformity and reproducibility. To address this, the present study investigated the effects of dynamic MF exposure on the germination and early growth of Khao Dawk Mali 105 (KDML 105) rice seeds. A novel MF testing apparatus was developed using a 150 mT permanent magnet and a vortex-based air injection system designed to continuously rotate and redistribute seeds, ensuring uniform exposure. Seeds were treated for 0, 5, 10, 15, and 20 min to evaluate effects on vigor, germination, and seedling growth. The results showed that 5 and 10 min exposures significantly enhanced seed vigor (93.00% and 94.67%, respectively) compared to the control (83.33%), with 10 min yielding the highest improvement (p < 0.05, DMRT). Shoot and root growth also increased by 14.21% and 99.59%, respectively. These findings suggest that moderate-duration dynamic MF exposure is an efficient, eco-friendly priming technique for improving seed vigor and early growth. Future research should explore long-term agronomic impacts, economic feasibility, and varietal responses. The apparatus’s scalable design supports integration into industrial seed processing lines, advancing sustainable rice production.